2017
DOI: 10.1093/gerona/glx126
|View full text |Cite
|
Sign up to set email alerts
|

Low Alanine Aminotransferase Levels in the Elderly Population: Frailty, Disability, Sarcopenia, and Reduced Survival

Abstract: These results suggest that reduced ALT levels in older individuals can be considered as a marker of frailty, disability, and sarcopenia, and as an independent predictor of adverse outcomes. The possible relationship between reduced ALT and impaired hepatic metabolic functions should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
100
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 35 publications
16
100
1
1
Order By: Relevance
“…The present study with proper confounder adjustment confirmed the results of a previous study without confounder adjustment in terms of the association between low ALT and LOI . Moreover, the results of our study were consistent with those of previous studies of the elderly evaluating the independent association between low ALT and death . However, Le Couteur et al .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present study with proper confounder adjustment confirmed the results of a previous study without confounder adjustment in terms of the association between low ALT and LOI . Moreover, the results of our study were consistent with those of previous studies of the elderly evaluating the independent association between low ALT and death . However, Le Couteur et al .…”
Section: Discussionsupporting
confidence: 92%
“…Although there was no information regarding the causes of LOI in our study, we expect that the causes of LOI were similar between our study and national statistics because of our population‐based cohort study design with a high follow‐up rate. In terms of cause‐specific death, a previous study also showed the association between low ALT and cardiovascular death, although respiratory disease death was not evaluated . We assume that low ALT is associated with LOI or death through various adverse events such as dementia, cardiovascular diseases including stroke, and respiratory disease.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations